PENGELOLAAN PROSES PEMBELAJARAN BAGI ANAK BERKEBUTUHAN KHUSUS PADA KELAS INKLUSI DI SD KEPUHAN BANTUL TAHUN PELAJARAN 2015/2016 - Ipuk Rahmah Hayati; FX Sindhuredja (Universitas Sarjanawiyata Tamansiswa, 2016)
This research is aimed to describe the learning process management for the inclusion class of chilren with special needs at SD Negeri Kepuhan Bantul school year 2015/2016. This research type is descriptive qualitative. The subjects of the study consisted of a principal, teacher classroom, teachers special assistants, students, and parents of children with special needs. Data was collected through interviews, observation, and documentation. The data obtained are tested its validity by increasing persistence, triangulation, and using reference materials. The data analysis technique that is performed with data collection, data reduction, data presentation, and conclusion. The results of the research showed that: a) the management of the learning process at SD Negeri Kepuhan, include: (1) the learning plan; (2) the implementation of learning; (3) assessment of learning outcomes. b) the problem faced by the teacher learning process of the children with special needs were: (1) lack of GPK; (2) some of the classes are too many students with special needs; (3) teachers have difficulty in dealing with students Tuna Grahita; (4) the lack of cooperation of parents. c) Evaluation of the management of the implementation of inclusive education and learning management at SD Negeri Kepuhan, namely:(1) the overall evaluation of the implementation of inclusive education conducted by a questionnaire from Dikpora and the respondence is Principals and Teachers; (2) Evaluation of the learning management conducted by the Principal and parents.